The Relationship between Patient Centered Care Implementation and the Quality of Health Services at the Regional General Hospital Dr. RM Djoelham Binjai 2022 - Sukma Yunita (Science Midwifery, 2022)
Hospitals are services that have an important role in people's lives in the health sector, Patient Centered Care (PCC) is related to seven patient safety standards that can improve health services in general hospitals, at the Dr. RM Djoelham Binjai has been accredited Plenary and has implemented PCC, but it has not been carried out optimally and has never been studied before regarding the relationship between PCC implementation and the quality of health services in the Inpatient Room of Dr. Hospital. RM Binjai, the purpose of the study was to determine whether the relationship between the implementation of patient centered care and the quality of health services at the Dr. RM Djoelham Binjai in 2022. This research uses this type of research using direct observation, using a cross sectional research approach, the study population was all patients who were hospitalized at the Regional General Hospital Dr. RM Djoelham Binjai in 2022 as many as 63 patients, the sample in the study was total sampling, the research technique used the chi square formula (kai squared). The results of this study show that there is a significant relationship between the implementation of Patient Centered Care and the Quality of Health Services at the Dr. Regional General Hospital. RM Djoelham Binjai in 2022, with p value = 0.002 (p<0.05). The conclusion in this study from these results. There is a significant relationship between the implementation of Patient Centered Care with the Quality of Health Services at the Dr. Regional General Hospital. RM Djoelham Binjai, suggestions for health workers need to do training related to information and communication to patients and families